Yap and Taz are required for Ret-dependent urinary tract morphogenesis - Reginensi, Antoine (Development, 2015)
Despite the high occurrence of congenital abnormalities of the lower urinary tract in humans, the molecular, cellular and morphological aspects of their development are still poorly understood. Here, we use a conditional knockout approach to inactivate within the nephric duct (ND) lineage the two effectors of the Hippo pathway, Yap and Taz. Deletion of Yap leads to hydronephrotic kidneys with blind-ending megaureters at birth. In Yap mutants, the ND successfully migrates towards, and contacts, the cloaca. However, close analysis reveals that the tip of the Yap(−/−) ND forms an aberrant connection with the cloaca and does not properly insert into the cloaca, leading to later detachment of the ND from the cloaca. Taz deletion from the ND does not cause any defect, but analysis of Yap(−/−);Taz(−/−) NDs indicates that both genes play partially redundant roles in ureterovesical junction formation. Aspects of the Yap(−/−) phenotype resemble hypersensitivity to RET signaling, including excess budding of the ND, increased phospho-ERK and increased expression of Crlf1, Sprouty1, Etv4 and Etv5. Importantly, the Yap(ND)(−/−) ND phenotype can be largely rescued by reducing Ret gene dosage. Taken together, these results suggest that disrupting Yap/Taz activities enhances Ret pathway activity and contributes to pathogenesis of lower urinary tract defects in human infants.